2003
DOI: 10.1021/bi035511n
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Cph1 Phytochrome Assembly from Stopped-Flow Kinetics and Circular Dichroism

Abstract: The kinetics and mechanism of the autocatalytic assembly of holo-Cph1 phytochrome (from Synechocystis) from the apoprotein and the bilin chromophores phycocyanobilin (PCB) and phycoerythrobilin (PEB) were investigated by stopped flow and circular dichroism. At 1:1 stoichiometry, pH 7.9, and 10 degrees C, SVD analysis of the kinetic data for PCB revealed three spectral components involving three transitions with time constants tau(1) approximately 150 ms, tau(2) approximately 2.5 s, and tau(3) approximately 50 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
97
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(112 citation statements)
references
References 50 publications
13
97
1
Order By: Relevance
“…5). Similar Soret features are seen in Cph1 and in plant phytochromes (32,45,46); therefore, a similar interpretation would seem likely for those proteins as well. We conclude that significant structural heterogeneity of the bilin configuration itself must exist in the P fr state, even though previous studies demonstrate structural rigidity of the phytochrome P fr state (71) and apparent P fr homogeneity on an ultrafast timescale (72).…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…5). Similar Soret features are seen in Cph1 and in plant phytochromes (32,45,46); therefore, a similar interpretation would seem likely for those proteins as well. We conclude that significant structural heterogeneity of the bilin configuration itself must exist in the P fr state, even though previous studies demonstrate structural rigidity of the phytochrome P fr state (71) and apparent P fr homogeneity on an ultrafast timescale (72).…”
Section: Discussionsupporting
confidence: 58%
“…4A). In the P fr state, we observed positive far-red CD and complex Soret features that were similar to those of the model cyanobacterial phytochrome Cph1 (32,46). In surprising contrast, the orange/far-red NpyrPHY1 exhibited negative far-red CD but similar Soret features (Fig.…”
Section: Gwitgps1 Fromsupporting
confidence: 64%
See 2 more Smart Citations
“…In this regard, examination of chromophore assembly with Cph1 by stoppedflow spectrophotometry (Borucki et al, 2003) demonstrated that assembly involves three key steps: initial noncovalent binding of PCB to the Cph1 apoprotein in a cyclic, porphyrin-like conformation, formation of a more extended red-shifted PCB Á apoCph1 intermediate, and covalent bond formation concomitant with a spectral blue shift. The red-shifted intermediate is thought to reflect chromophore protonation and adoption of the more extended configuration characteristic of Pr.…”
Section: Structure and Assembly Of The Phytochrome Photosensory Corementioning
confidence: 99%